Effects of larval exposure to the insecticide flumethrin on the development of honeybee (Apis mellifera) workers - Liu, Chen; Wu, Xiaobo; Yang, Heyan; Yu, Longtao; Zhang, Yong (Frontiers in Physiology, 2022)
Flumethrin is a widely used acaricide, but its improper use often leads to residue accumulation in honeybee colonies, thus threatening the health of honeybees, especially at the larval stage. Therefore, this study aimed to describe the direct toxicity of flumethrin on honeybee (Apis mellifera) larvae by conducting bioassays for immune and detoxification-related enzymes and transcriptome sequencing to determine the potential effects on newly emerged adults who were exposed to flumethrin during the larval stage. Results showed that the higher the concentration of flumethrin the honeybee larvae were exposed to, the greater the damage to the physiology of honeybee larvae and the newly emerged worker bees. When honeybee larvae were exposed to flumethrin concentrations higher than 0.01 mg/L, the activities of glutathione sulfur transferase (GST) and carboxylesterase (CarE) were affected, and the metabolism-related genes in the head of newly emerged honeybees exposed to flumethrin during the larval stage were down-regulated. Flumethrin concentration higher than 0.1 mg/L significantly increased mixed-functional oxidase (MFO) content in honeybee larvae, reduced the larval survival rate, and down-regulated the expression levels of olfactory-related and antioxidant-related genes in newly emerged honeybees. Furthermore, a flumethrin concentration of 1 mg/L significantly down-regulated the expression levels of immune and detoxification-related genes in newly emerged honeybees. These findings provide a comprehensive understanding of the response of honeybee larvae to sublethal flumethrin toxicity and could be used to further investigate the complex molecular mechanisms in honeybees under pesticide stress.